Effects of the Lipid Metabolites and the Gut Microbiota in ApoE−/− Mice on Atherosclerosis Co-Depression From the Microbiota-Gut-Brain Axis - Hu, Ke; Liao, Xing-Xing; Wu, Xiao-Yun; Wang, Rui; Hu, Zi-Wei; Liu, Si-Yuan; He, Wen-Fen; Zhou, Jun-Jie (Frontiers in Molecular Biosciences, 2022)
To investigate the changes of lipid metabolites in the prefrontal cortex and hippocampus regions and the characteristics of the gut microbiota in ApoE-/- mice with atherosclerosis co-depression. ApoE-/- mice (HFB group, n=14,♂) fed a high-fat diet for 16 weeks with binding stimulation were used as an animal model for atherosclerosis co-depression. Compared with NC group mice, HFB group mice showed depression-like behaviors and atherosclerosis-related pathological indicators. Non-targeted lipidomics analysis by LC-MS/MS showed that the different lipid metabolites in the prefrontal cortex and hippocampus regions of HFB and NC groups were mainly LPC, LPE, LPS, PC, PE, PS, PI, and GD1a, and were mainly enriched in the glycerophospholipid metabolism pathway and the retrograde endocannabinoid signaling pathway, which leads to abnormal white matter and synaptic dysfunction. Sequencing of 16S rDNA amplicons revealed significant differences in the structure of the gut microbial community between the two groups. Compared with the NC group, the abundance of Deferribacteres and Proteobacteria in the HFB group increased, while the abundance of Verrucomicrobia and Actinobacteria decreased at the phylum level; the abundance of Desulfovibrio, Clostridium_IV, Helicobacter, and Pseudoflavonifractor increased, while the abundance of Akkermansia decreased at the genus level, resulting in increased gut inflammation and decreased gut permeability, which leads to the release of inflammatory cytokines. Finally, the correlation analysis results showed that the above-mentioned differential lipid metabolites had a strong correlation with the differential gut microbiota.